Transitional Care Nurses' Self-Reported Characteristics of Work Areas, Job Satisfaction, Competencies and Need for Further Training: A Cross-Sectional Study - Møller, Nicoline; Geil Kollerup, Mette; Lerbæk, Birgitte; Berthelsen, Connie (Integrative Journal of Medical Sciences, 2021)
Introduction: Transitional care for older people with multiple chronic conditions is complex, and identifying the competencies of the nurses who provide such care is essential. Aim: This study aimed to describe and compare the self-reported characteristics of transitional care nurses related to their work areas, job satisfaction, competencies, and need for further training. Methods: A cross-sectional study design was used, and STROBE was followed for reporting. The total population of transitional care nurses (n = 28) in Denmark was invited to participate. Data were collected through a questionnaire covering work areas, job satisfaction, competencies, and the need for further training. Results: Respondents reported high confidence in competencies related to direct clinical practice, cooperation and consultation, caregiver involvement, use of electronic communication, and a limited need for further training. Expert transitional care nurses have high confidence in their work competencies in terms of patients, administrative tasks, and increased job satisfaction.